Pembuatan Biodiesel Dari Minyak Biji Kapuk (Ceiba Pentandra) Dengan Katalis Lempung Teraktivasi; Pengaruh Konsentrasi Katalis Dan Aktivasi Katalis - Nurhasanah Nurhasanah; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is a methyl ester transesterification reaction products of triglycerides derived from vegetable oils or animal fats. One among of vegetable oils that can produce biodiesel is kapok seed oil. Kapok seed oil had higher levels of unsaturated fatty acids are high that they could be made to produce biodiesel. This research is aim to make biodiesel from kapok seed oil, studying the effect of concentration of activated clay catalyst to the amount of biodiesel produced, determine the characteristics of biodiesel from kapok seed oil and determine the best catalyst activation of the activation of acid or base. The transesterification process occured at a temperature of 60oC, the weight of oil 50 grams, the reaction time 1,5 hours, mole ratio of oil to methanol 1 : 9, variation of the catalyst concentration 0,1%, 0,5%, and 1%-weight of oil, and variations of acid solution (0,47%, 0,62%, dan 0,78%) and alkaline solution (0,33%, 0,44%, 0,66%) for activation of catalyst. From the result is obtained the highest biodiesel of 1% catalyst concentration of acid activation 0,78%, methanol mole ratio of 1: 9 for 1,5 hours as much as to 92,62 %. Characterization of physical properties of biodiesel is density of 871 kg/m3, 3,11 mm2/s kinematic viscosity, acid number 0.36 mg KOH / g sample, and the flash point 200oC respectivity.Keywords: biodiesel, catalysts, clay, activation of acids, activation of bases, transesterification